How social media usage can be integrated in market orientation and how the use of it influences performance? - Kaijala, Iiris (My University, 2020)
This thesis studies if social media usage can be integrated in market orientation and if this relationship influences performance. Social media can be identified as WEB 2.0 which allows companies and consumers to access different platforms and new ways of communicating and providing information. Companies using social media can leverage the level of market orientation and gather information from new markets and consumers. This study aims to see if market orientated companies have higher performance. Performance here is divided to market performance and finance performance to deepen the study. The influence to performance is studied with SPSS linear regression model to see if there is a correlation.
Keywords: social media; marketing; business; communication; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business